IRS reportedly preparing to give Musk’s Doge agency access to taxpayer data - Helmore, Edward (The Guardian, 2025)
US agency reviewing request for access to classified system containing personal financial records of US taxpayers.
Keywords: Elon Musk; Trump administration; US news; US politics